convert and write the equation in slope intercept form. y-3=2(x-1)

1 answer

To convert the given equation \( y - 3 = 2(x - 1) \) into slope-intercept form (which is \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept), follow these steps:

  1. Distribute the 2 on the right side: \[ y - 3 = 2x - 2 \]

  2. Add 3 to both sides to isolate \( y \): \[ y = 2x - 2 + 3 \]

  3. Simplify the right side: \[ y = 2x + 1 \]

So, the equation in slope-intercept form is: \[ y = 2x + 1 \]